Growth and nutrient accumulation in three peach rootstocks until the grafting stage - Menegatti, Renata Diane; Souza, Aline das Graças; Bianchi, Valmor João (Comunicata Scientiae, 2019)
Analysing growth and nutrient accumulation is generally employed for guiding the fertilisation practices in the seedling-production chain. In the production of peach rootstock, such evaluations can provide information to aid can to aid in discrimination available genotypes, especially regarding the efficient use and conversion of fertiliser into dry matter, which can reduce the time required to obtain plants suitable for grafting. The aim of this study, was to investigate the differences in growth and nutrient accumulation in three peach-rootstock cultivars. A completely randomised experimental design was used, in a 3 x 4 factorial scheme, including three peach rootstocks ('Flordaguard', 'Capdeboscq' and 'Okinawa Roxo') and four periods of growth evaluation (20, 40, 60 and 80 days after transplanting - DAT), giving a total of 12 treatments, with four replications, one for each plant. The Flordaguard and Capdeboscq cultivars showed greater height and stem diameter as well as a greater accumulation of total dry matter at 80 DAT, and both followed the distribution: leaves (67%) > roots (33%), while total dry-matter production in 'Okinawa Roxo' was less, following the order: leaves (71%) > roots (29%). The rootstock under evaluation showed variations in growth, confirmed by the physiological indices, except for the leaf area and specific leaf area. In general, macronutrient accumulation in the shoots and roots of the cultivars during each growth period was different, suggesting intrinsic differences in each of the genetic materials regarding nutrient demand for maintaining the metabolic processes which are vital to plant growth.